Pengaruh Persepsi Quality Dan Persepsi Nilai Terhadap Keputusan Pembelian Produk MS Glow Melalui Kepercayaan Sebagai Intervening Pada MS Glow Kota Padang - Nafisa Warosati Jannah (CV. ITTC INDONESIA, 2026)
This study aims to analyze the influence of perceived quality and perceived value on purchasing decisions for MS Glow products through trust as an intervening factor at MS Glow in Padang City. This study is an associative study with an unknown population and purposive sampling technique. Data were collected through questionnaires with a sample size of 96 respondents. Data analysis was conducted using hypothesis testing. The results showed that perceived quality and perceived value had a positive and significant effect on trust. Perceived quality and perceived value had a positive and significant effect on purchasing decisions. Trust also had a positive and significant effect on purchasing decisions. Trust was able to mediate the relationship between perceived quality and perceived value on purchasing decisions for MS Glow products at MS Glow in Padang City